1999
DOI: 10.1056/nejm199907013410102
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Evidence of an Association between Mitral-Valve Prolapse and Stroke in Young Patients

Abstract: Mitral-valve prolapse is considerably less common than previously reported among young patients with stroke or transient ischemic attack, including unexplained stroke, and no more common than among controls. Using more specific and currently accepted echocardiographic criteria, therefore, we could not demonstrate an association between the presence of mitral-valve prolapse and acute ischemic neurologic events in young people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(58 citation statements)
references
References 34 publications
2
49
1
6
Order By: Relevance
“…More recent observational cohort and case-control studies have not confirmed an association. [496][497][498] In the midst of some lingering uncertainty in this area, observational studies provide reassuring information that the risk for stroke in people with mitral valve prolapse is low (<1% annually). [499][500][501][502] No randomized trials have addressed the efficacy of antithrombotic therapies for this specific subgroup of stroke or TIA patients.…”
Section: Mitral Valve Regurgitation and Mitral Valve Prolapsementioning
confidence: 99%
“…More recent observational cohort and case-control studies have not confirmed an association. [496][497][498] In the midst of some lingering uncertainty in this area, observational studies provide reassuring information that the risk for stroke in people with mitral valve prolapse is low (<1% annually). [499][500][501][502] No randomized trials have addressed the efficacy of antithrombotic therapies for this specific subgroup of stroke or TIA patients.…”
Section: Mitral Valve Regurgitation and Mitral Valve Prolapsementioning
confidence: 99%
“…Our results however were discordant with Gilon et al (20) ,they performed a casecontrol study, and reviewed data on 213 consecutive patients 45 years of age or younger with documented ischemic stroke or transient ischemic attack. The prevalence of prolapse in these patients was compared with that in 263 control subjects without known heart disease.…”
Section: **Motor Deficitsupporting
confidence: 71%
“…There are also reports of shortened platelet survival and increased platelet coagulant activity in patients with cerebral embolism and mitral valve prolapse (Lewis, 1988). On the other hand, recent population based and case-control studies demonstrated no increased frequency of mitral valve prolapse among patients with stroke or transient ischemic attacks, including young patients (Gilon et al, 1999;Orenica et al, 1995;Petty et al, 1994). In addition, patients with mitral valve prolapse who had strokes were similar in age to the general stroke population, and many had other risk factors for strokes, including atrial fibrillation (Gilon etal., 1999;Nishimura et al, 1985;Orenica et al, 1995).…”
Section: Mitral Valve Prolapsementioning
confidence: 99%